PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR LOGIS SISWA SEKOLAH DASAR - Zelvia Efrianti; Muhammad Syahrul Rizal; Yenni Fitra Surya; Putri Hana Pebriana; Sumianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low logical thinking skills of fifth grade students of UPT SDN 011 Koto Tuo. The purpose of this study is to improve the logical thinking skills of fifth grade students of UPT SDN 011 Koto Tuo by implementing the PBL model. This type of research is classroom action research (CAR). This research was conducted in 2 cycles and each cycle was conducted in two meetings. The subjects of this study were 18 fifth grade students of UPT SDN 011 Koto Tuo. Data collection techniques used in the study were observation, documentation and test techniques. Based on the results of the study, it can be concluded that students' logical thinking skills increased in each cycle, where the percentage results in cycle I meeting I were 44%, cycle I meeting II 50%, cycle II meeting I 56% and cycle II meeting II 61%. Thus, it can be concluded that the application of the PBL model in Ipas learning can improve the logical thinking skills of fifth grade students of UPT SDN 011 Koto Tuo. Further strategies or modifications to the approach are needed so that learning outcomes can be maximized.